Evaluation of Heavy Silicon Oil in the Treatment of Retinal Detachment Mainly Iinvolving Lower Quadrants - Adam Cywiński (Okulistyka)
Introduction: The article presents a retrospective analysis of postoperative, anatomic results, including complications in a group with diagnosed primary and recurrent retinal detachment, involving the lower quadrants, where heavy silicon oil was used.